A study on the effect of the flow rate on the power produced by the pico hydropower - Wan Mohamad Azam, Wan Mahmod (2013)
This thesis deals with the study on the effect of flow rate on the power generated by the Pico hydropower. The objective of this study is to study the relationship of the flow rate and the power generated by the Pico hydropower. The objective of this thesis also is to make the result obtained from the study as a benchmark for the further research on the power generated by the Pico hydropower. The experiment was conducted by using the pump that has the function similarly as the Pelton turbine. The potential energy created by the stream of the water is converted to mechanical energy and the mechanical energy will rotate the blade of the turbine. As the blade of the turbine is rotated, the magnetic field inside the generator been cut and the induction of electric will happen. As the result, the electrical power is produced by the turbine. All the analysis and data collected is done by using Dasy lab software. The obtained result shows that the value of flow rate affect the power generated by the turbine. The value of power generated by the turbine increase as the flow rate increase. The minimum and the maximum value of the power generated also are obtained from the experiment. The result also indicates that difference value of the voltage will generate difference power. The results concluded that the power generated by the turbine is depends on the flow rate because the high flow rate will created enough energy to rotate the blade of the turbine and at the same time the electrical power is produced. The results obtained are very significant as a benchmark for the further research on the power generated by the Pico hydropower.